Effect of Biofloc product‐Rapid BFTTM vs. clear water system in improving the water quality and growth performances of Pacific Whiteleg shrimp, P. vannamei, cultured in indoor aquaculture system. (8th August 2021) - Kasan, Nor Azman; Manan, Hidayah; Tuan Ismail, Tuan Ismarani; Abdul Salam, Amir Ihsan; Abdul Rahim, Ahmad Ideris; Kamarruzan, Amyra Suryatie; Ishak, Ahmad Najmi; Deraman, Shuhaimi; Nasrin, Zuhayra; Che Engku Chik, Che Engku Noramalina; Che Hashim, Nurul Fakriah; Terkula Iber, Benedict
Abstract: Biofloc technology was known to improve the shrimp growth performance and water quality in several ways. The application of bacterial booster was proven to accelerate the development of biofloc in the culture treatments as well as help improve the water quality, shrimp growth performance and yield production. Due to its importance, a study was conducted to identify the effect of biofloc application using Rapid BFT TM microbial booster formulation versus clear water system to improve shrimp growth performance and water quality condition. Study was conducted for 80 days with every 7 days of interval of data collection. Overall, biofloc treatments were identified successfully in improving the shrimp growth performance and also effectively reduced the nutrient concentrations of total ammonia nitrogen (TAN) from the biofloc culture treatments until the end of culture periods. Nitrate (NO3 − ) from biofloc treatments was also identified in lower concentration as compared to control of clear water system. The average daily growth (ADG) was at 0.12g much better from biofloc treatments as compared to control with ADG 0.08g of clear water system. The specific growth rate (SGR) was 5.47%/day in biofloc and 2.82%/day in control treatments which identified higher and much better from biofloc about 2.65%/day differences between biofloc and clear water. Meanwhile, the final body weight achieved was much higher from biofloc about 9.55 grams compared with control about 7.06 grams from the same day of culture, DOC80 which recorded at the end of cultured period. The first sampling was started at DOC7 where the average initial weight of shrimp in biofloc treatment was 0.117 grams and 0.077 grams identified in control. The highest biomass achieved from biofloc treatments also much better around 11.0 kg compared with control that produced 7.1 kg as the higher biomass produced. There was only yellow and green colony of Vibrio identified from the TCBS culture and no occurrence of luminescent colony from harmful Vibrio harveyi detected. Therefore, it can be concluded that biofloc technology of Rapid BFT TM help improves the water quality of ammonia nitrogen level in water columns and inhibits pathogenic Vibrio to the culture species as well as help improving the shrimp growth performances in more effective way.